Survival Math for Marketers. - Weiglin, Peter C. (SAGE Publications, 2002)
This book provides an introduction to the underlying mathematical concepts in marketing and management in terms accessible to students of all levels. Weiglin also explains the relevant non-mathematical issues, such as price sensitivity, product distribution, and sales estimates, and provides the tools necessary to fully understand the basics of each. Presented in an irreverent, conversational style, this book includes numerous real-world examples and illustrations that gently introduce the reader to the important mathematical concepts behind marketing and management. Intended for stud.